Palaeoecological investigations and 230Th/U dating of the Eemian Interglacial peat sequence from Neubrandenburg-Hinterste Mühle (Mecklenburg-Western Pomerania, NE Germany). (20th February 2018) - Börner, Andreas; Hrynowiecka, Anna; Stachowicz-Rybka, Renata; Niska, Monika; Moskal-del Hoyo, Magdalena; Kuznetsov, Vladislav; Maksimov, Fedor; Petrov, Aleksey
Abstract: The Eemian Interglacial sequence was explored in the gravel pit 'Neubrandenburg-Hinterste Mühle' near Neubrandenburg (NE Germany). The sequence is situated in a former kettle hole depression between underlying Late Saalian till (s. str. Warthe) covered by a Late Weichselian till. Today still visible a 3 m long and max. 2 m wide profile is located on the edge of the former Eemian depression. The limnic sedimentation began during the Late Saalian in a landscape characterized by open herbaceous vegetation. Cool, clear and calcium carbonate-rich lake water dominated, inhabited by Characeae that indicates a presence of stonewort meadows, most typical of waters up to 10 m in depth. The beginning of the Eemian Interglacial succession was characterized by a dominance of scarce birch forest followed by pine forest. The beginning of the mesocratic phase of the Eemian was characterized by the appearance of warm climate indicators and by the development of thermophilic forest communities dominated by oak forest with the appearance of warm climate indicators. The ensuing climate optimum was defined by the encroachment of hazel-oak forest and later by mixed deciduous forest. Limnic sedimentation ceased in the basin during this phase and the end of predominantly limnic conditions is marked by a decrease in the frequency of aquatic plants and an increase in the amount of brown mosses. During the interglacial optimum mixed forests reigned. This phase bears a record of oligotrophication leading to transition mire and raised bog and the aquatic plants vanished. The depression gradually became shallower and was overgrown by a forest cover. During the telocratic phase of the Eemian, communities with pine, birch and fir spread. The end of the interglacial was characterized by a disappearance of the riparian forest and a sporadic appearance of reedswamp plants. At the beginning of the Early Weichselian, a deterioration of climatic conditions resulted in the formation of widespread heaths on acid soils and trees disappeared. In the studied basin the water level fluctuated. The Hinterste Mühle sequence shows the development of a small kettle hole lake and its transformation to an overgrowing mire, including terrestrialization processes, during the Eemian Interglacial. The U/Th data obtained for five samples from the upper part of the studied profile, which have been analyzed by the TSD technique, has yielded an age of 116 ± 13/10 kyr. This date reflects the classification into the second half of the Eemian Interglacial and the Early Weichselian for the upper part of peat formation.